Pola Asuh Orang Tua terhadap Psikis Anak dalam Tiga Cerpen Indonesia - Utami*, Zahwa Febby; Sarifah, Riski Nur (Universitas Suryakanca, 2024)
The focus of this article is on the parenting pattern depicted in the short story by Leila S. Chudori entitled